Factors that Influence Caesarean Section Delivery at Columbia Asia Hospital Medan - Dewi Eva Imawati Sinaga; Thomson P; Asriwati Asriwati (Journal La Medihealtico, 2022)
Delivery is the process of expelling the products of conception (fetus and placenta). Caesarean section is a delivery in which the fetus is born through an incision in the front wall of the abdomen and uterine wall with the condition that the uterus is intact and the fetal weight is above 4000 grams. The purpose of this study was to determine and analyze the delivery of Caesarean section at Columbia Asia Hospital Medan in 2020.This study used a quantitative method with a cross sectional design, with a research sample of 40 respondents. This study used a questionnaire. The research was conducted on March-October 2021 as a follow-up to the end of the research. The analysis of this study used Univariate, Bivariate and Multivariate. The statistical test used chi square test and logistic regressionThe results of the study on the effect of Age (P-value 0.000), Parity (P-value 0.000), Knowledge (P-value .003), Trust (P-value 0.000), Childbirth Indications (P-value 0.001), Anxiety (P-value .002), Husband's Perception (P-value .001) and based on the logistic regression test of age, parity, confidence, labor indications, anxiety, husband's perception were variables that affect the delivery of cesarean section.The conclusion in this study shows that there is a significant influence between age, anxiety and work on cesarean delivery. It is suggested and expected to midwives on duty at Columbia Asia Hospital Medan City to provide health education about family planning to mothers after giving birth so that pregnancy does not occur before 2 years.